Genetic analysis of Toxocara cati (Nematoda: Ascarididae) from Guangdong province, subtropical China. (2nd January 2018) - He, Xi; Lv, Meng-Na; Liu, Guo-Hua; Lin, Rui-Qing
Abstract: Toxocara cati (cat roundworm) is a common parasitic nematode that infects humans and other hosts, causing toxocariasis. Although its significance as a pathogen, the epidemiology, genetics and biology of T. cati remain poorly understand in China. In the present study, genetic variation in mitochondrial (mt) cytochrome c oxidase subunit 1 ( cox 1) gene and internal transcribed spacer (ITS) of rDNA region among T. cati in Guangdong province, subtropical China was examined. A portion of the cox 1 (p cox 1) and the complete ITS (ITS1 + 5.8S rDNA + ITS2) were amplified separately from individual worms by polymerase chain reaction (PCR) and amplicons were then subjected to sequencing from both directions. The length of the sequences of p cox 1, ITS-1, and ITS-2 were 308 bp, 462 bp, and 335 bp, respectively. The intra-specific sequence variations within T. cati were 0–3.6% for p cox 1, 0–2.4% for ITS-1, and 0–2.7% for ITS-2. However, the inter-specific sequence differences were significantly higher, being 8.6%, 10.7%, and 11.3% for p cox 1, ITS-1, and ITS-2, respectively. Phylogenetic analyses based on the p cox 1 sequences indicated that all the isolates in Guangdong province were in genus Toxocara, which confirmed that these parasites represent T. cati . The molecular approach employed provides a powerful tool for elucidating the epidemiology, genetics, and biology of zoonotic T. cati in China and elsewhere.